PENGARUH PENERAPAN KEBIJAKAN PROGRAM PENGUNGKAPAN SUKARELA (PPS) / TAX AMNESTY JILID II DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Clarina Freshya Waruwu; Lorina Siregar Sudjiman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The purpose of this research is to determine the effect of the Voluntary Disclosure Program and tax sanctions on taxpayer compliance. This research used 37 respondent taxpayers from various regions. The data collection method for this research is the questionnaire method, which is distributed online with google forms on a likert scale of 1-5 points and processed using SPSS application. Data analysis techniques include descriptive statistical, validity test, reliability test, coefficient of determination test (Adjusted R Square), simple linear test and correlation coefficient test. The results of the study indicate that the Voluntary Disclosure Program has a significant effect on taxpayer compliance and tax sanctions had no effect on taxpayers.